The Influence of Student-Generative AI Interaction on Self-Regulated Learning and Academic Achievement - Salem Belhaj (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: Generative Artificial Intelligence (GAI) shocked the world with its remarkable ability and delivered considerable tensions associated with the educational system. As educators navigate their futurist role in education, it will inevitably involve GAI in some form rather than working to avoid it. Understanding the facilitator process between students and their interaction with GAI tools and their resulting performance is important to us as educators and as schools, however, there is a paucity of relevant empirical evidence. The current study aim to examined that students-GAI interaction has impact on self-regulated learning and learning achievement, via mediating effects of self-efficacy and creative cognition among undergraduate students across Tunisia. Methodology: 378 design students from Tunisian universities participated in physical surveys as part of a quantitative approach for data collection. The study used 5-point Likert scales to assess students’ self-efficacy, creative cognition, self-regulated learning and learning achievement, and GAI interaction. SmartPLS 3.0 was used for both direct and mediation analysis of the data. Findings: The findings demonstrated that the interaction between students and GAI strongly predicted learning achievement (H2), self-regulated learning (H1), self-efficacy (H3–H4), and creative cognition (H5–H6). Implications/Novel Contribution: The results provide actual support for integrating GAI into educational programs. These results offer insightful information to educators and policymakers, indicating that design curricula that use GAI can greatly improve designer skills, encourage academic success, and nurture creative cognition. In the rapidly changing educational landscape of today, it is essential to comprehend how AI affects students’ creative processes in order to build effective teaching tactics.